An Emerging Health Care Trend: Mobile Health - Munazza Saleem, (Pakistan Journal of Medical & Health Sciences, 2022)
The health care industry is extremely competitive, and to satisfy patients' expectations and streamline hospital functioning, mobile health (mHealth) is an adequate tool. From easy appointment scheduling to reducing unnecessary emergency visits and uncomplicated billing to active health promotion, mobile health can help patients meet their requirements, boost hospital productivity, and enhance patients' health outcomes. A literature search was carried out to identify referenced content and gather relevant articles as the knowledge foundation to develop this paper. This article intends to reflect on the various aspects of mHealth. This paper begins with an overview of mHealth, followed by the recent literature analysis, advantages and challenges associated with this new trend, and a prediction of the future of mHealth. It is the opinion of this paper that mHealth is the future tool for the provision of better healthcare and that it will revolutionize the way healthcare is delivered.